دراسة الصخور المسامية وتشوهاتها تحت تأثير الحمولات الخارجية والضغط المسامي - خضور, عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة الصخور المسامية المشبعة تحت تأثير الحمولات الخارجية والضغط المسامي. سوف نشرح في المرحلة الأولى كيف تتم طريقة تعيين الثوابت الميكانيكية والهيدروليكية تجريبياً, وذلك من خلال نظرية المرونة. أما في المرحلة الثانية فسنعمل على توضيح تأثير ظهور التشققات ضمن الكتلة الصخرية الناتجة عن الحمولات الخارجية على العلاقة بين الضغط المسامي والتشوهات في الكتلة الصخرية.حيث إن سلوك الكتل الصخرية غير خطي يعود وبشكل أساسي إلى ظهور هذه التشققات الناتجة عن التحميل, يكون اتجاه هذه التشققات دائماً عمودياً على اتجاه الإجهادات الصغيرة.ونظراً لأن هذه الشقوق وضمن هذه المعطيات هي موجهة فمن الطبيعي أن العلاقة بين الضغط المسامي والتشوهات في الكتلة الصخرية ستصبح غير متجانسة. This research tries to study saturated and porous rocks under the effect of outside loads and the pore pressure. In the first stage, we will explain how the hydraulic and mechanic constants are determined experimentally. In the second stage, we will clear out the effect of the appearance of cracks within the rock mass resulting from the outside loads, and the effect of these cracks on the relation between the pore pressure and the deformation within the rock mass. Since the non-liner behavior of the rock mass is essentially due to the appearance of these cracks resulting from loading. The direction of these cracks is always perpendicular to the direction of the minor stresses. Because these cracks within these data are directed, it is natural that the relation between the porous pressure and the distortions within the rock mass will become heterogeneous.